3D printed self powered soft-bio robotics - Tan, Suan Yang (Nanyang Technological University, 2022)
Robotics is at the forefront of human technology and has a far reach, affecting all areas of our life. A field in which robotics can have an extensive impact and extensively contribute is in the field of medicine, it could give rise to the development of nano-robots able to enter the human body to perform a platitude of medical tasks. As such, there has been a frenzy in the development of technologies to produce robots that have suitable properties that allow them to enter the human body safely to perform these tasks. At the cutting edge of this are soft-bio robots made of hydrogels that can enter the body safely and form soft actuators to create motion. Of key interest is developing ways to create robots that are self-propelled and thus less reliant on external power supplies. As such we have endeavoured to explore, research and design methods that will enable us to create such a self-powered robot. Implementing a chemical base reaction using hydrogen peroxide and manganese oxide to propel the robot, after having refined the design of the robot. Experiments were then conducted to examine how different concentrations of manganese oxide would affect the performance and propulsion of the robot, we also sought to see the effect that different designs may have on the hydrodynamics of the robot. Intriguingly it was found that despite what was thought, adding a cone does not help with the propulsion of the robot.